Expert Testimony in Superior Court, Québec, Case No. 05-04841-72, Chief Robert Kanatewat, et al. vs James Bay Development Corporation, et al. and The Attorney General of Canada, January 10, 1973 - Feit, Harvey A. (1973)
Cree and Inuit hunters and their families were the witnesses who convinced the judge to rule that the Project should be stopped while other court cases proceeded (although this stoppage turned out to be brief). I saw my role as providing expert testimony that supplemented what Cree, as unacknowledged experts, were permitted and not permitted to say in court. That their presence and statements were central to the judge’s ruling was clear from his citations of witnesses and his use of some of their terms and concepts in his text. Alongside this, he also cited considerable evidence in support of his conclusions from testimonies of those who were allowed to speak as expert witnesses. This testimony was given in the James Bay Cree’s court case for an interlocutory injection to stop the James Bay Hydro-electric Project construction while other court proceedings considered the recognition of their Aboriginal rights. As an interlocutory proceeding the focus was on damages that Cree would suffer in the short-term if the Project continued, and whether these effects could be remedied. This is “expert” witness testimony, even though Cree were clearly the experts. Court procedures constrained what witnesses could say. Cree and those without expert standing in the court were often challenged by lawyers when their statements went beyond what they knew at first hand from observation and experience. Expert witnesses could testify based on other kinds of statements and evidence, including about collective social patterns, what was said as common discourse, and what aggregated information, statistical records, and historical documents showed. They were mainly challenged based on Euro-Canadian research methodologies and the validity of their statements. My testimony, along with that of others, addressed some of the basic claims that governments and corporations were making about Cree to the media and in the courtroom. These included: Cree were now living like other Québecers; they no longer used the land or hunted any differently ...